Anna De Soto: capstone - De Soto, Anna, artist (Colorado State University. Libraries, 2026)
The artist's statement: Memory Misattunement came from thinking about my childhood. So many times in therapy or when talking about childhood things with friends I find it hard to figure out if a memory is true or not; or struggling to have a clear memory at all. I know my childhood was fun and happy but I also know that there were some fairly traumatic events that I can not clearly remember. I attribute this to growing up as an only child. I have never had a peer my age to reflect or bounce memories off of. I grew up a latchkey kid meaning I was alone everyday after school because both of my parents had full time jobs. This "aloneness" is something I remember being fun and full of imagination but have I misremembered it? My mom recalls how lonely I was and how much I longed to have siblings. My capstone explores memory and imagination through fiber works, weaving and felting specifically. The natural gaps in weaving lends to gaps in memory. The softness of felting lends itself to the soft foggy haze of a fleeting memory. Each piece represents a happy memory of childhood that also has sadness and loneliness directly attached to it. Blank Memories is the happy memories but also grieving the loss of some of those memories. Kinda Looks Like… is the memory of being outside and imagining cloud shapes but only by myself. What's Left of My Backyard, the centerpiece of my show, represents my happy but fleeting memories of playing in my backyard with my dog; going on adventures and playing in imaginary worlds, alone. My last piece, Bad Dreams, is not a happy memory but more of a representation of my memory of how afraid I was of being alone while falling asleep and some of it translating into my day. Other pieces I have included I found important to show my full portfolio of pieces I've made in my time at CSU.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers